Division of Labor Among Transgender and Gender Non-binary Parents: Association With Individual, Couple, and Children’s Behavioral Outcomes - Tornello, Samantha L. (Frontiers in Psychology, 2020)
The division of unpaid labor is an important aspect in understanding co-parenting dynamics, along with individual well-being, couple functioning, and family dynamics. This study explores the division of household and childcare unpaid labor, well-being, relationship functioning, and child behavioral outcomes in 163 transgender and gender non-binary (TGNB) parents. Research exploring the division of labor among cisgender heterosexual couples has found that cisgender women in heterosexual couples disproportionately conduct more of the household and childcare labor (e.g., Lachance-Grzlea & Bouchard, 2010). In addition, among heterosexual (e.g., Lachance-Grzlea & Bouchard, 2010) and same-sex couples (Tornello, Sonnenberg, & Patterson, 2015), discrepancies in the division of unpaid labor has been associated with individual well-being, along with couple functioning. We know very little about the factors that predict how labor is divided, along with the impact these arrangements among of families headed by TGNB parents. In this study, TGNB parents reported dividing their household and childcare labor in an egalitarian fashion and wanted to divide their labor in that way. The gender of participants, gender design of the couple, educational attainment, and legal status of the couple’s relationship were not associated with the division of unpaid labor. In contrast, participants who reported making a lower proportion of the household income, worked less hours in paid employment, and were genetically related to their eldest child, reported completing significantly more childcare-related tasks, but not household labor. Using multiple regressions, participants’ genetic relatedness to their eldest child was the only significant predictor of performing greater unpaid childcare labor. Lastly, discrepancies in the household, but not childcare labor, predicted parental well-being and couple functioning. The division of labor among TGNB couples was unrelated to their child behavior outcomes. This study not only sheds light on the dynamics of TGNB-headed families, but also additional factors that influence the division of unpaid labor and how this division affects individuals within the family system.